First report of Anisakis simplex (Nematoda, Anisakidae) in the sea lamprey (Petromyzon marinus) - Bao, Miguel; Garci, Manuel E.; Antonio, José Manuel; Pascual, Santiago (Food Control, 2013)
6 páginas, 5 figuras, 2 tablas A total of 64 sea lampreys Petromyzon marinus caught in Galician rivers in 2012 (NW Spain), were dissected and examined for evaluate the presence of marine parasitic Anisakidae nematodes following microscopic and PCR analysis. The results revealed that sea lampreys are infected by third-larval stage of Anisakis simplex. Internal organs, especially the gonads, and flesh, hosted from 1 to 10 Anisakis larvae with prevalence values reaching up to 60%. This is the first time that this infection is registered in the sea lamprey. The plausible hypothesis is that sea lamprey might has acquired larvae once feeding on flesh or the products of tissue cytolysis from infected teleosts (e.g. Atlantic salmon). In Galician waters, the sea lamprey could act as a transport host for A. simplex from marine to freshwater ecosystems. This finding has epidemiological relevance considering the zoonotic and gastro-allergic condition of this parasite. Peer reviewed